Multirresistant bacteria and their impacts on public health: A social responsability (Research, Society and Development, 2021)
Introduction: Human beings coexist with numerous bacteria, but pathogenic species have plagued mankind for millennia until the advent of the first antibiotics. However, the indiscriminate use of antibiotics, both in hospitals and in agriculture, has generated high rates of bacterial resistance and has become a problem with imminent disruption. The present study aims to analyze the multifactorial etiology of bacterial multiresistance mechanisms, the prevalence of the main bacteria involved in this process and its impact on public health. Methodology: This is an integrative literature review about the processes and consequences of bacterial resistance. The inclusion criterion was compatibility with the theme and relevance. Results: 46 articles were analyzed, half of which are original articles. Among these, 6 articles carried out a survey of the prevalence of pharmacoresistant bacteria in nosocomial environments, with a sample of 646 patients in which Klebsiella pneumoniae was isolated in 27.11%, Pseudomonas aeruginosa in 19%, followed by Escherichia coli with 16%, and Staphylococcus aureus with 4.75%. Discussion: With 25 to 50% of antibiotic administrations in hospitals considered irregular, their indiscriminate use and the slow formulation of new therapeutic options, among others, contributed to the development of multidrug-resistant bacterial strains during the antimicrobial era. The main pharmacoresistance mechanisms include antibiotic modification; preventing the action of the antibiotic on its target; alteration of the primary binding site; and producing an alternative target to circumvent the drug's effect. Final Considerations: Bacterial multidrug resistance increases morbidity and mortality, length of hospital stay and expenses with supplies and specialized staff. It was established as a problem that tends to worsen over time, therefore, comprehensive studies focused on bacterial prevalence are necessary to outline public health strategies aimed at its control.